2002
DOI: 10.1053/bbmt.2002.v8.pm12434948
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cell contamination of blood stem cell products in patients with metastatic breast cancer: Predictors and clinical relevance

Abstract: The incidence and clinical relevance of tumor cells contaminating the stem cell products of patients with advanced breast cancer treated with high-dose chemotherapy is uncertain because prior studies used small sample sizes and lacked standardization of the immunocytochemistry (ICC) detection method used. We evaluated blood stem cell and bone marrow samples obtained from 535 women with metastatic breast cancer who received high-dose chemotherapy and unmanipulated mobilized blood stem cell support. Of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
2
20
1
1
Order By: Relevance
“…The hematologic recovery at 30 days after transplant was also more complete after PBSC than after bone marrow transplantation. An additional advantage of PBSC is the lower risk that PBSC are contaminated with tumor cells that may reside in the bone marrow [41]. Few studies have systematically addressed this issue, but the few studies support the common sense of this approach.…”
Section: Why Use Peripheral Blood In Stead Of Bone Marrow?mentioning
confidence: 99%
“…The hematologic recovery at 30 days after transplant was also more complete after PBSC than after bone marrow transplantation. An additional advantage of PBSC is the lower risk that PBSC are contaminated with tumor cells that may reside in the bone marrow [41]. Few studies have systematically addressed this issue, but the few studies support the common sense of this approach.…”
Section: Why Use Peripheral Blood In Stead Of Bone Marrow?mentioning
confidence: 99%
“…Several naturally occurring or engineered oncolytic viruses are emerging as novel tools for selective growth in and killing of a variety of tumor cells (1,21,34,41). It has been consistently reported that during tumor evolution, diminished interferon (IFN) responsiveness coevolves as a frequent genetic defect (4,31,32,41).…”
mentioning
confidence: 99%
“…[10][11][12]15,16 In the setting of high-dose chemotherapy and autologous stem cell transplant, isolated tumor cells have been found in the BM and in the aphereses of patients undergoing progenitor cell harvest and autografting, 27 and in some reports this finding correlated with a worse event-free survival. 28,29 Methods for determining MRD in the BM and peripheral blood of breast cancer patients include immunocytochemistry, immunohistochemistry, and RT-PCR of relevant breast cancer-associated genes. MMG is a protein associated with most breast cancers, and RT-PCR determination of MMG expression in BM has been found to be specific and sensitive.…”
Section: Discussionmentioning
confidence: 99%